Magnetic and dynamic mechanical properties of a highly coercive MRE based on NdFeB particles and a stiff matrix. (25th August 2020) - Hermann, S; Butaud, P; Chevallier, G; Manceau, J-F; Espanet, C
Abstract: This study concerns a magnetorheological elastomer (MRE) consisting of a magnetically hard powder and a stiff polymer matrix, so called STH–MRE. This material exhibits some strong constitutive differences with the behavior of MRE based on soft polymer matrix and magnetically hard powder (SOH–MRE). This paper presents a manufacturing process for such a STH–MRE, describes testing procedures to get the magnetic properties, the viscoelastic behavior and the magneto-mechanical coupling generated by the remanent magnetization, and shares the STH–MRE properties with the scientific community. Firstly, the manufacturing process is detailed. Then, the homogenized magnetic properties and their dependence on the volume fraction and the temperature are discussed. Thereafter, dynamic mechanical analysis is explained and the viscoelastic properties are discussed considering the polymer matrix properties, the volume fraction and the temperature. Magneto-mechanical couplings are investigated in absence of an external magnetic field. The coercive field strength of composite material and powder are almost equal while the remanent flux density depends on volume fraction. The temperature dependence of the magnetic properties is given as well as homogenization rules. The viscoelastic data of the STH–MRE are provided in a large temperature range and in the mechanical vibration frequency range. The magneto-mechanical coupling due to the remanent magnetization is shown to be negligible.